Dividing by Zero. Tautology and Paradox in the Self-Descriptions of Anonymous - Beraldo, Davide (Journal of Sociocybernetics, 2020)
This paper engages with the loosely bounded, ill-defined Anonymous movement, in order to develop a theoretical reflection on the process of self-reference within contemporary collectives. It is grounded on a socio-cybernetic framework and builds on a computationallly-assisted interpretative analysis of a huge dataset of Facebook posts related to Anonymous’ self-descriptions. As selected examples show, Anonymous results inherently contradictory. Its boundaries are radically contingent and performative, to the extent that it is impossible to distinguish the authentic from the inauthentic. The collective defines itself as ontologically multiple and radically anti-essentialist. Moreover, whereas Anonymous’ actions are systematically contradictory, Anonymous self-descriptions, relying on arguments mirroring poststructuralist theories, can only be tautologically or paradoxically expressed. Building on Luhmann’s claim that the reproduction of modern societies depends on concealing their self-referential foundations, the conclusion argues that Anonymous, by embracing its own constitutive paradox, pushes the process of autopoiesis to a new, radically recursive logic, departing in this even from recent theorizations on reflexivity.